2020
DOI: 10.1177/0022034520937617
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b Promotes Subchondral Bone Loss in TMJ Osteoarthritis

Abstract: Abnormal subchondral bone remodeling plays important roles during osteoarthritis (OA) pathology. Recent studies show that bone marrow mesenchymal stem cells (BMSCs) in osteoarthritic subchondral bones exhibit a prominent pro-osteoclastic effect that contributes to abnormal subchondral bone remodeling; however, the pathologic mechanism remains unclear. In the present study, we used a mouse model with OA-like change in the temporomandibular joint (TMJ) induced by an experimentally unilateral anterior crossbite (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…In vivo, we adopted UAC model which could produce abnormalities in bite force direction and distribution to mimic the natural pathogenesis process of aberrant occlusion-induced TMJOA in human beings as previously described. 21 , 27 , 28 Micro-CT analysis results suggested a decrease of BMD, BV/TV, Tb.Th, and Tb.N in UAC group while Tb.Sp was increased when compared to sham controls ( Figure 7A ). mRNA expression level of Col2 and Sox9 was downregulated, Cox-2 and Mmp13 was upregulated in UAC group ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 95%
“…In vivo, we adopted UAC model which could produce abnormalities in bite force direction and distribution to mimic the natural pathogenesis process of aberrant occlusion-induced TMJOA in human beings as previously described. 21 , 27 , 28 Micro-CT analysis results suggested a decrease of BMD, BV/TV, Tb.Th, and Tb.N in UAC group while Tb.Sp was increased when compared to sham controls ( Figure 7A ). mRNA expression level of Col2 and Sox9 was downregulated, Cox-2 and Mmp13 was upregulated in UAC group ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 95%
“…Studies have reported that bone marrow mesenchymal stem cells (BMSCs) in osteoarthritic subchondral bones show a prominent pro‐osteoclastic activity, resulting in the abnormal subchondral bone remodelling 38,39 . Sun 40 demonstrated that there was subchondral bone loss and osteoclast hyperfunction in UAC mice, and it could be rescued by BMSC‐specific overexpression of miR‐29b by aptamer‐agomiR‐29b. Additionally, it has been found that overextension of the mandible induced subchondral bone loss in the early stages, and osteoblasts and osteoclasts of the condyle subchondral bone were activated 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It predominantly involves the destruction of articular cartilage, although there is also a gradual degeneration and loss of the subchondral bone that lies adjacent to cartilage tissue and provides it with nutritional and mechanical support. [ 67 , 68 ] The role of subchondral bone in OA pathology has gained more attention in recent years, with the gradual realization that the pathophysiology of OA involves intimate cross talk between subchondral bone and articular cartilage. [ 69 , 70 ] Indeed, a functional complex known as the bone–cartilage unit is formed by subchondral bone and cartilage, which is implicated in OA pathophysiology at the mechanical and biochemical levels.…”
Section: Bone Tissue Degeneration and Loss Under Various Disease Cond...mentioning
confidence: 99%